2014
DOI: 10.3109/08958378.2014.922648
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ozone induces a systemic inflammatory response: possible source of the neurological alterations induced by this gas

Abstract: The World Health Organization identified urban outdoor air pollution as the eighth highest mortality risk factor in high-income countries. Exposure to ambient pollutants such as ozone (O3) increases the number of hospital admissions. O3 is a highly reactive gas that reacts with cells lining the airways, producing the formation of reactive oxygen species and inflammation. Beyond the respiratory system, O3 exposure also produces fatigue, lethargy, headaches, and significant decrease in rapid-eye-movement sleep r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…In our O 3 exposure paradigm, we did not observe the hallmarks of neuroinflammation, such as reactive gliosis or up-regulation of proinflammatory cytokines in the brain. This is seemingly in contrast to the findings of other groups, who have reported that reactive microgliosis or the induction of proinflammatory cytokines in the brain occurs in O 3 -exposed rats (9,87). It is possible that species differences could account for different neuroinflammatory responses, and a potentially important difference in rats vs. mice is that SAA is not a major acute-phase protein in rats (31); however, a recent study by Mumaw et al (8) reported an observation of microgliosis in O 3 -exposed mice.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our O 3 exposure paradigm, we did not observe the hallmarks of neuroinflammation, such as reactive gliosis or up-regulation of proinflammatory cytokines in the brain. This is seemingly in contrast to the findings of other groups, who have reported that reactive microgliosis or the induction of proinflammatory cytokines in the brain occurs in O 3 -exposed rats (9,87). It is possible that species differences could account for different neuroinflammatory responses, and a potentially important difference in rats vs. mice is that SAA is not a major acute-phase protein in rats (31); however, a recent study by Mumaw et al (8) reported an observation of microgliosis in O 3 -exposed mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the most prevalent toxicants in polluted air, O 3 has been associated with respiratory and cardiovascularrelated health issues and, more recently, has been implicated in CNS dysfunction. Such dysfunctions include cognitive decline and dementia (2)(3)(4), increased stroke risk (5)(6)(7), neuroinflammation and oxidative stress (8)(9)(10)(11)(12), and accumulation of amyloid-b and a-synuclein that are pathologic proteins in Alzheimer's disease and Parkinson's disease, respectively (11)(12)(13)(14)(15); however, the mechanisms by which O 3 exposure could adversely affect CNS function remain unknown. We posit that O 3 inhalation elevates circulating proinflammatory mediators that can access the CNS by crossing the blood-brain barrier (BBB).…”
mentioning
confidence: 99%
“…Exposure to O 3 induces the formation of RONS and inflammatory cytokines in the lung tissue and the olfactory tract. In the CNS, these molecules are capable of activating NF- κ B that promotes the expression of proinflammatory genes [57, 58]. Our results showed an increase in the activation of NF- κ B in the acute phase of exposure while chronic exposure to O 3 showed a decreased activation of NF- κ B in the rat hippocampus.…”
Section: Discussionmentioning
confidence: 58%
“…To determine the expression of the GAD isoforms in the RN, western blot assays were performed as previously described (Gonzalez‐Guevara et al, ). In brief, GAD 65 was localized using a mouse monoclonal antibody (Santa Cruz, Biotechnology, Cat # sc‐377145, RRID: AB_2619725) (Table ), and GAD 67 was localized using a mouse monoclonal antibody (Santa Cruz Biotechnology, Cat # sc‐28376, RRID: AB_627650).…”
Section: Methodsmentioning
confidence: 99%